INTERAKSI ANTARA PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA DENGAN PENDEKATAN OPEN-ENDED DAN KEMAMPUAN AWAL MATEMATIS (KAM) SISWA - Nasution, Eline Yanti Putri (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2017)
This article aims to examine the interaction between improving students’ creative thinking ability toward the learning approach that is the End-Ended Approach and Conventional Learning and Mathematical Early Skills (KAM) of the students. The research was conducted in one of State Junior High School with population of all students of class VIII. Two classes were selected from the population as a sample of the research using purposive sampling technique. Conventional Learning is implemented in the control class and the Open-Ended approach is implemented in the experimental class. This research uses the instrument of creative thinking ability test to see the improvement of students’ creative thinking ability. The data processing of students’ creative thinking ability based on mathematical early ability (KAM) is done by using two–way ANOVA test at 5% significance level (α = 0,05). followed by Post Hoc LSD test. Based on data analysis result, it is obtained: (1) there is a difference  of improvement of creative thinking ability between students who gain learning by using Open-Ended approach with  students who abtained Conventional Learning from the Mathematicsl Beginning Skill (KAM) of students; (2) there is no interaction between the learning approaches (Open-Ended and Conventional) and students’ Mathematical Abilities (high, medium, and low) towards improving students’ creative thinking ability; (3) students show positive attitudes toward the Open Ended approach. This study  is a learning factor and theoretical ability of the students does not provide the same effect on the students’ creative thinking ability.